Santri Delinquency From Social Psychology Perspective - Azam Syukur Rahmatullah (Tribakti: Jurnal Pemikiran Keislaman, 2022)
Juvenile delinquency occurs anywhere and anytime, including in Islamic boarding schools. Several studies have shown that students’ problematic behavior is sometimes strange and deviates from the rules of the Islamic boarding school. Therefore, the researcher seeks to deeply examine the juvenile delinquency of students in the Islamic boarding school community. This research is literature research, descriptive research, qualitative research, and exploratory which examines in-depth literature based on General and Social Psychology on Islamic boarding schools to find new aspects related to juvenile delinquency of santri. The analysis used a content analysis study and an in-depth discussion of the written information contents. The results indicated that juvenile delinquency students stem from unhealthy behavior; among the causes; are psychic instability, superego deficiency, control, and defective perceptual function. The therapy for problem students is cognitive behavioral therapy or Cognitive Behavior Modification, which combines cognitive and behavioral approaches to solve problems. Some efforts were: first, initial assessment and diagnosis; second, looking for the root of the problem from negative emotions, thought process deviations, and central beliefs related to the disorder; third, an intervention plan prepared by the counselor to provide positive-negative consequences for counseling; fourth, status formulation, therapeutic focus, behavioral intervention, and fifth is relapse prevention and self-help training